APLIKASI EKSEKUTIF BERBASIS M-COMMERCE (STUDI KASUS PADA CV ZEUS CAR AUDIO & ACCESSORIES SEMARANG) (Information Technology and Telematics, 2013)
M-commerce is all electronic transactions are done using mobile devices and mobile networks that lead to thetransfer of value is considered true and the exchange of information, goods, or services (www.mobileinfo.com).M-Commerce has an important role at this time in order to pamper the consumer, because all kinds of transactionscan be done anytime and anywhere through mobile media devices. CV Zeus Car Audio & Accessories is a companyengaged in the sales of car audio. The booking system is currently running is still running slow. The purpose of thisresearch is to create an application that will make booking car audio products especially through mobile mediadevices to obtain the booking system is more effective and efficient and can reach out to the wider community in theIndonesian region. The method used is the waterfall method, namely requirements, design, coding, testing,maintenance. The advantages of this application are the payment methods provided by the Bank Transfer and CashOn Delivery. The application is built using a programming-based WAP and PHP, and XHTML, using the MySQLdatabase and using Apache webserver.Keywords: Mobile Commerce, WAP, Waterfall, Car Audio